Peran Bimbingan Penyuluhan Pendidikan Islam dalam Menghindari Perilaku Negatif - Fuadi, Anwar (Global Education Journal, 2023)
Increasing worship for police officers is crucial, especially if it is connected to the "negative stigma" that police officers face in society, as it will be beneficial to them in doing their responsibilities. The goal of this study was to ascertain how spiritual and mental advice may be used to counteract the harmful conduct of the Banjarmasin Polsek. This study employs descriptive qualitative methods. Triangulation is the method employed, which includes interviews, observation, and documentation. The study's findings indicate that the process of offering spiritual and mental counseling to Banjarmasin Police officers greatly encourages them to participate more actively in religious worship so that they can promote peace, feel content, safe, and protected, and are always protected.